Projeto urbanístico para o Vale do Rio Jahu (perímetro urbano do município de Jahu): projeto paisagístico - Picchia, Paulo Celso Dornelles Del; Cavalheiro, Felisberto [UNESP] (Sociedade Botânica do Brasil, 1987)
Em 1974 a Prefeitura Municipal de Jahu interessada na urbanização do vale do Rio Jahu no trecho urbano propôs a abertura de avenidas marginais, conforme previa o plano diretor. Os autores preocupados com as potencialidades de uso do vale, sugeriram que se afastasse as avenidas do rio e se desse a oportunidade da criação de um parque às margens do rio. Esse parque teria a função de integrar o rio à paisagem urbana, compatibilizando, ao mesmo tempo, os interesses sociais da população com as necessidades da conservação da natureza.

In 1974 Jahu's Municipal Administration was interested in the urbanization of the urban section of the valley of the Jahu river, proposed the opening of riverside drives as stated in the Urban Structure Plan. The authors concerned with the potenciality on the use of the valley suggested that the drives could be pushed aside from the riverside in order to provide an opportunity in the creation of a park on the riverside. That park would have the function in integrating the river and the urban landscape and in addition would harmonize the population social interests with the needs of nature conservation.
Keywords: City Planning; Landscape Planning; Nature Conservation; Open Spaces; Outdoor Recreation